Industrial training report: DKT Engineering Sdn Bhd. / Aiman Fatihah Aziz - Aziz, Aiman Fatihah (Universiti Teknologi MARA, Perlis, 2021)
My unforgettable internship program started at DKT Engineering Sdn Bhd. In this report I will talk about the company’s background, what I did during my internship and my overall analysis of the company. This report provides all the details. I will discuss SWOT analysis and PESTEL analysis based on the facts and observations made. During the internship, I mainly worked in Account and Finance department and have been described in detail. Since the purpose of this internship program is to learn how to put into practice what I have learned every semester and to give us a picture of the real world. I also gained new insights, experience and meet new friends through this internship program. With the current Covid-19 issue, we still have to work in the office. This internship report covers many important aspects and essentially everything relating to the company and all processes, practices and procedures I followed and studied during my internship days. It also contains my suggestions for the company’s future activities and leadership.